Precariousness of everyday heroism. A biographical approach to life politics - Ahponen, Pirkkoliisa (Qualitative Sociology Review, 2005)
It is a special challenge for an individual to be the hero of his/her own life in the social conditions of reflexive modernisation. Autobiographies are not only descriptions of what happened during the life course, but they also reflect individual capacity to construct cultural identities in reflexive and reflective ways. To reflect on one’s own success, personal gains and losses have to be compared with the competitive capacities of other community members of the hierarchically structured society. Reflexive capacity is the demand to become a conscious self and culturally identified member of a social group. Selfidentity is reconstructed and coped with in light of meaningful others during certain transition periods in the life course. Life-political meaningfulness is checked by overcoming personal difficulties in order to manage life-challenges further. Self-respect gives the resources needed for overcoming alienating experiences, for controlling the risk of social exclusion and for mastering one’s own life successfully. Narrative identification of self tends to produce life-heroes. But the problem considered relevant here starts from reflecting altruism with reflexive monitoring of the self. The question is whether heroic episodes of life can be narrated so that heroic everyday deeds are emphasised in autobiographies. Or is everyday heroism present only in precarious moments which escape ego-centrism because this kind of heroism can be placed only at the social margin, where surviving a difficult situation obliges one to turn unselfishly toward another?